Hva legitimerer filosofi i Norge? - Espen Gamlund (Norsk Filosofisk Tidsskrift)
Abstract It is a useful exercise to reflect, sometimes, on the way philosophy is carried out, and on how we think philosophy should be carried out in the future. We need to accept that academia is undergoing some important changes, which means that academic philosophy is also changing. The aim of this article is to discuss what gives philosophy its legitimacy in Norway. I will argue that the justification for having philosophy in Norway, in one way or the other, must be that it has societal value. In this respect, I believe that teaching and public outreach are philosophy's most important areas of focus. Even though I mainly concentrate on academic philosophy in Norway, much of what I say is relevant for understanding the legitimacy of academic philosophy in other countries.